Aspects of life quality of persons with physical disabilities - Mockevičienė, Daiva; Savenkovienė, Agnė (Social Welfare: Interdisciplinary Approach, 2012)
The article presents the problems of the involvement of persons with disability into applied physical activity, indicators of physical activeness, life satisfaction and attitude towards one’s disability. In the research the indicators of life quality of persons with physical disability who are involved in sports activities and who are not involved in sports activities have been compared. 111 persons with physical disability who have experienced traumas of spinal cord participated in the research. The results of the questionnaire survey have shown that the respondents with physical disability who go in for sports feel bigger life satisfaction, assess their psychical health more favourably than those who are not involved in sports. The attitude towards one’s disability among persons with disability who are involved in sports is much more favourable than among those who are not. Persons with disability who are involved in physical and sport activity tend to rely more on their strengths even when favourable conditions are not created for them. Meanwhile, the unadjusted environment more often hinders the respondents not involved in sports from feeling like an able person of full value. The indicators of life satisfaction and attitude towards one’s disability among persons with disability who participate in sport activity are better than among those who do not participate.